Intracellular Calcium and the Mechanism of Anodal Supernormal Excitability in Langendorff Perfused Rabbit Ventricles - Joung, Boyoung (2011)
BACKGROUND: Anodal stimulation hyperpolarizes cell membrane and increases intracellular Ca(2+) (Ca(i)) transient. This study tested the hypothesis that The maximum slope of Ca(i) decline (–(dCa(i)/dt)(max)) corresponds to the timing of anodal dip on the strength-interval curve and the initiation of repetitive responses and ventricular fibrillation (VF) after a premature stimulus (S(2)). METHODS AND RESULTS: We simultaneously mapped membrane potential (V(m)) and Ca(i) in 23 rabbit ventricles. A dip was observed on the anodal strength-interval curve. During the anodal dip, ventricles were captured by anodal break excitation directly under the S(2) electrode. The Ca(i) following anodal stimuli is larger than that following cathodal stimuli. The S(1)-S(2) intervals of the anodal dip (203 ± 10 ms) coincided with the -(dCa(i)/dt)(max) (199 ± 10 ms, p=NS). BAPTA-AM (n=3), I(NCX) inhibition by low extracellular Na(+) (n=3), and combined ryanodine and thapsigargin infusion (n=2) eliminated the anodal supernormality. Strong S(2) during the relative refractory period (n=5) induced 29 repetitive responses and 10 VF episodes. The interval between S(2) and the first non-driven beat was coincidental with the time of -(dCa(i)/dt)(max). CONCLUSIONS: Larger Ca(i) transient and I(NCX) activation induced by anodal stimulation produces anodal supernormality. Time of maximum I(NCX) activation is coincidental to the induction of non- driven beats from the Ca(i) sinkhole after a strong premature stimulation.